Arte; belleza y amor: una ventana a lo trascendente (2010)
In the present work we attempt to make an introduction to the study of art as a way of encounter with the mysterious and the ineffable. We will rely; on the one hand; on the thoughts of great artists; philosophers and critics of art; such as Tarkovsky; Picasso; Unamuno and Steiner; and; on the other hand; on the contributions made by Christian theology and Christian iconography. We will approach the work of art in the key of hope: through inner silence and contemplation we may find the voice of another Beauty which attracts us towards itself; showing us how Love; Beauty; Goodness and Truth are different sides of reality which transcends death; pain and lie